2015
DOI: 10.1108/jtf-03-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility improvement interventions realised in Byzantine monuments of Thessaloniki, Greece

Abstract: Purpose-Access to culture is a fundamental right of people with disabilities and a significant aspect in the development of accessible tourism. A visit to a monument provides an authentic experience which cannot be substituted by any representation. However, any interventions to improve accessibility should be made carefully, so as not to alter the monument's character, or damage it visually or structurally. The paper aims to discuss these issues. Design/methodology/approach-A theoretical approach model was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, service provision and amenities are important even for them. Infrastructure (Durgamohan, 2015; Jauhari, 2009a), police force (Tyagi and Dhar, 2014); disabled accessibility (Naniopoulos and Tsalis, 2015; Naniopoulos et al , 2015, 2016); flood planning (Ganguly and Rai, 2016; Kabra and Ramesh, 2015), transportation (Sharma and Sharma, 2015), and improved services and facilities (Babu and Munjal, 2015; Hung et al , 2015; Jauhari, 2009b) are important in religious tourism as well. Kartal et al (2015) include the proper recruitment and training of religious tourism personnel along with the lack of co-ordination between local and central governmental organisations among the issues.…”
Section: Resultsmentioning
confidence: 99%
“…However, service provision and amenities are important even for them. Infrastructure (Durgamohan, 2015; Jauhari, 2009a), police force (Tyagi and Dhar, 2014); disabled accessibility (Naniopoulos and Tsalis, 2015; Naniopoulos et al , 2015, 2016); flood planning (Ganguly and Rai, 2016; Kabra and Ramesh, 2015), transportation (Sharma and Sharma, 2015), and improved services and facilities (Babu and Munjal, 2015; Hung et al , 2015; Jauhari, 2009b) are important in religious tourism as well. Kartal et al (2015) include the proper recruitment and training of religious tourism personnel along with the lack of co-ordination between local and central governmental organisations among the issues.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that tactile material or replicas included in a museum can have a profound impact on visually impaired visitors, allowing them to acquire information about the objects they are touching [37]. For the same reason, museums may use multisensory approaches, including tactile collections and replicas, handling sessions, audio guides and verbal assistance [39], or means of high technology such as virtual, and mixed reality applications [33], to provide a more accessible experience to visitors with visual impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Accessibility in a museum entails more than just physical access; [39] equally vital is access to information, which aids in comprehending the exhibition space [40]. Cognitive and sensory access should also be addressed and, where possible, adjustments should be made to reduce or remove existing barriers [41].…”
Section: Inclusive and Accessible Museumsmentioning
confidence: 99%